Formacion de educadores matematicos en la universidad de Nari~no: Etnomatematica y Cognicion - Blanco Alvarez, Hilbert; Marmolejo Avenia, Gustavo A. (Revista SIGMA, 2016)
Abstract This article presents a characterization of the fundamentals of both lines Ethnomathematics and Cognition and its contribution to the training of graduates in mathematics at the University of Nari~no. In addition, it exposes contributions in research, social projection and publications in each of these lines. Resumen Se presenta una caracterizacion de los fundamentos de las lneas de Etnomatematica y Cognicion y su aporte a la formacion de Licenciados en Matematicas en la Universidad de Nari~no. As mismo, se exponen los aportes en investigacion, proyeccion social y publicaciones en cada una de estas lneas.